2019
DOI: 10.3390/jcm8101634
|View full text |Cite
|
Sign up to set email alerts
|

Alternations of Circadian Clock Genes Expression and Oscillation in Obstructive Sleep Apnea

Abstract: Circadian misalignment plays an important role in disease processes and can affect disease severity, treatment outcomes, and even survivorship. In this study, we aim to investigate whether expression and daily oscillation patterns of core circadian clock genes were disturbed in patients with obstructive sleep apnea/hypopnea (OSA) syndrome. We performed real-time quantitative reverse transcriptase-polymerase chain reactions to examine the expression of the nine core circadian clock genes in leukocytes of periph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
39
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 29 publications
3
39
2
Order By: Relevance
“…Whether these metabolic disruptions are perpetuated by chronic hyperglycemia or sleep breathing disorders remains to be elucidated. Similarly, the combined downregulation in the expressions of CRY1 and PER3 at midnight predicted the severity of the disease in patients with obstructive sleep apnea/hypopnea syndrome [18]. Additionally, in patients with type 2 diabetes, those with the poorest sleep quality showed a dampened mRNA expression of clock genes such as BMAL1 and PER1 [33].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Whether these metabolic disruptions are perpetuated by chronic hyperglycemia or sleep breathing disorders remains to be elucidated. Similarly, the combined downregulation in the expressions of CRY1 and PER3 at midnight predicted the severity of the disease in patients with obstructive sleep apnea/hypopnea syndrome [18]. Additionally, in patients with type 2 diabetes, those with the poorest sleep quality showed a dampened mRNA expression of clock genes such as BMAL1 and PER1 [33].…”
Section: Discussionmentioning
confidence: 94%
“…Until now, there have been limited reports on the relationships between regulation of oxygen homeostasis and circadian clock genes in type 2 diabetes [18,19]. To further increase our knowledge in this emerging field, we have designed a study to examine whether the expression of HIF-α subunits (HIF-1α and HIF-2α) is connected with changes in the expression of eight core circadian clock genes according to the presence of type 2 diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…Although there is limited data on the role of the circadian clock in OSA ( von Allmen et al, 2018 ; Yang et al, 2019 ; Gabryelska et al, 2020 ), it may play a significant role in this disease ( Entzian et al, 1996 ; Smith et al, 2017 ; Butler et al, 2015 ). We found dysregulation of circadian gene expression in multiple cell types.…”
Section: Discussionmentioning
confidence: 99%
“…Sleep disorder was associated with a higher AF recurrence rate in patients receiving either medication or ablation therapy [ 16 ]. Additionally, sleep disorder will cause alternations in circadian clock genes expression and oscillation [ 17 ]. Our previous study found that sleep disorders can affect the performance of physiological clock genes of PB total leukocytes, and cause disease, such as sudden deafness [ 13 ].…”
Section: Discussionmentioning
confidence: 99%